(untitled) (Studia theodisca, 2020)
This article focuses on Monika Maron’s Krähengekrächz (2016) and Munin oder Chaos im Kopf (2018). Adopting the approach of Literary Animal Studies, it primarily analyses the diegetic creature “crow”: the species “crow” as well as its individual exponent Munin, which is anthropomorphized, disposes of speech and agency and represents not just a narrated “object” but a narrating “subject”. Subsequently, Maron’s crow-narrations, concretizations of a metanarration / a (cultural) narrative “crow”, are shaped in their relationship to fictional (literature) and factual (popular science) narratives of the crow and evaluated on their importance for current animal-discourses.